SOLUBILITY, DUCTILITY AND RESILIENCE OF A PMMA DENTURE RESIN WITH GRAPHENE AND SILVER NANOPARTICLES ADDITION - BACALI, Cecilia; BUDURU, Smaranda; NĂSTASE, Vivi; CRĂCIUN, Antarinia; PRODAN, Doina; CONSTANTINIUC, Mariana; BADEA, Mîndra Eugenia; MOLDOVAN, Marioara; SAROSI, Liana-Codruța (Studia Universitatis Babeș-Bolyai Chemia, 2019)
PMMA denture base materials are used for several decades without significant improvements in their composition. The addition of different fillers has been proved to improve some of the acrylic resin’s characteristics. Recent studies focused on enhancing PMMA properties using nanoparticles. In our study we assessed the effect of adding graphene and silver nanoparticles on the solubility, ductility and resilience of a commercial denture base acrylic resin.